Sensory sensitivity and symptom severity represent unique dimensions of chronic pain: a MAPP Research Network study. Issue 10 (October 2018) - Schrepf, Andrew; Williams, David A.; Gallop, Robert; Naliboff, Bruce D.; Basu, Neil; Kaplan, Chelsea; Harper, Daniel E.; Landis, J. Richard; Clemens, J. Quentin; Strachan, Eric; Griffith, James W.; Afari, Niloofar; et al.
Abstract : Abstract: Chronic overlapping pain conditions (COPCs) are characterized by aberrant central nervous system processing of pain. This "centralized pain" phenotype has been described using a large and diverse set of symptom domains, including the spatial distribution of pain, pain intensity, fatigue, mood imbalances, cognitive dysfunction, altered somatic sensations, and hypersensitivity to external stimuli. Here, we used 3 cohorts, including patients with urologic chronic pelvic pain syndrome, a mixed pain cohort with other COPCs, and healthy individuals (total n = 1039) from the Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network to explore the factor structure of symptoms of centralized pain. Using exploratory and confirmatory factor analysis, we identified 2 general factors in all 3 cohorts, one characterized by a broad increased sensitivity to internal somatic sensations, environmental stimuli, and diffuse pain, termed Generalized Sensory Sensitivity, and one characterized by constitutional symptoms—Sleep, Pain, Affect, Cognition, Energy (SPACE). Longitudinal analyses in the urologic chronic pelvic pain syndrome cohort found the same 2-factor structure at month 6 and 1 year, suggesting that the 2-factor structure is reproducible over time. In secondary analyses, we found that Generalized Sensory Sensitivity particularly is associated with the presence of comorbid COPCs, whereas SPACE shows modest associations with measures of disability and urinary symptoms. These factors may represent an important and distinct continuum of symptoms that are indicative of the centralized pain phenotype at high levels. Future research of COPCs should accommodate the measurement of each factor. Abstract : Supplemental Digital Content is Available in the Text.The symptomology of what has been called centralized pain can be described as 2 clusters, each related to different aspects of the clinical pain experience.